Evaluation of the prognostic value of CD3, CD8, and FOXP3 mRNA expression in early‐stage breast cancer patients treated with anthracycline‐based adjuvant chemotherapy. (21st September 2018) - Tsiatas, Marinos; Kalogeras, Konstantine T.; Manousou, Kyriaki; Wirtz, Ralph M.; Gogas, Helen; Veltrup, Elke; Zagouri, Flora; Lazaridis, Georgios; Koutras, Angelos; Christodoulou, Christos; Pentheroudakis, George; Petraki, Constantina; et al.
Abstract: Background: Tumor‐infiltrating lymphocytes (TILs) have been shown to be of prognostic value in several cancer types. In early breast cancer, TILs have a prognostic utility, as well, especially in HER2‐positive and triple‐negative breast cancer. TILs presence is broadly associated with improved survival; however, there is controversy regarding TILs subpopulations. Patients and methods: Early‐stage breast cancer patients treated with anthracycline‐based chemotherapy within two randomized trials were included in the study. We evaluated, by qRT‐PCR, 826 tumor tissue samples for mRNA expression of CD3, CD8, and FOXP3 for potential prognostic significance in terms of disease‐free survival (DFS) and overall survival (OS). Results: After a median follow‐up of 133.0 months, 255 patients (30.9%) had died and 314 (38.0%) had disease progression. In the univariate analysis, high CD3 and CD8 mRNA expression was found to be of favorable prognostic value for DFS ( P  = 0.007 and P  = 0.016, respectively). In multivariate analyses, the association of high CD8 mRNA expression with increased DFS was retained (HR = 0.77, 95% CI 0.60‐0.998, Wald's P  = 0.048), whereas that of high CD3 mRNA expression was of marginal statistical significance (HR = 0.77, 95% CI 0.59‐1.01, P  = 0.059). Moreover, a significant interaction was observed between HER2 status and CD3 mRNA expression with respect to DFS (interaction P  = 0.032). In the HER2‐positive subgroup, the hazard ratio associated with high CD3 mRNA expression was of greater magnitude (HR = 0.48, 95% CI 0.30‐0.76, P  = 0.002) compared with the hazard ratio presented above, for the entire cohort. No significant findings were observed for FOXP3 in terms of DFS, while none of the studied markers were of prognostic value for OS. Conclusions: High CD3 and CD8 mRNA expression in early‐stage breast cancer patients is of prognostic value for decreased risk of relapse and, in the future, could potentially be of importance in deciding the most appropriate therapeutic strategy in light of the recent immune‐related treatment developments. Abstract : We used CD3, CD8, and FOXP3 mRNA expression as markers for T cell infiltration, in early breast cancer patients treated with anthracycline‐based adjuvant chemotherapy. Results showed that high CD8 mRNA expression is associated with improved outcome in breast cancer and such prognostic value is more profound in the HER2‐positive subtype.